DIGITAL HERITAGE PORTAL BASED ON PROGRESSIVE WEB APP: EFFORTS FOR THE DEVELOPMENT OF CULTURAL HERITAGE AND TOURISM IN LAMPUNG - Brilliant, Muhamad; Nurhasanah, Iis Ariska; Oktaria, Herlini; Handoko, Dwi (TEKNOKOM, 2024)
According to Undang-undang No. 11 Th. 2010 regarding Cultural Heritage, preservation involves dynamic efforts to safeguard the existence and values of Cultural Heritage through protection, development, and utilization. Despite rapid technological progress, there is currently no dedicated digital platform designed to promote and preserve cultural heritage in Lampung Province. The diverse cultural legacies could be better harnessed and developed, as they hold significant potential for attracting tourists to the region. This research aims to design a Progressive Web App-based Digital Heritage Portal to foster cultural heritage and tourism in Lampung Province. Digital Heritage employs technology to understand and conserve cultural legacies. As an innovative approach, the information system is crafted using Progressive Web App technology for easy user access online or offline, without requiring prior app installation. The system is anticipated to aid in the promotion, preservation, and advancement of cultural heritage and tourism in Lampung. The research follows the Waterfall method with these stages: 1) Problem analysis, (2) Data collection, (3) System requirement analysis, (4) Coding, (5) Deployment, and (6) System testing. The research yields an application design functioning as an informative platform for historical and cultural heritage tourism in Lampung Province. The application operates smoothly across platforms and offline. Test results affirm proper menu functionality aligned with stipulated system requirements.